Effect of heating and cooling technique on residual compressive strength and weight loss of grout containing High volume fly ash. (January 2019) - Balakrishnan, B; Khalid, N H A; Ismail, M
Abstract: Grouting technology is commonly used in building and bridge construction as structural repair and gap filling material. However, the parent concrete is often mixed with conventional OPC cement-sand grout. In the event of fire, both concrete material and the grouts in structures are likely exposed to high temperatures which could results in premature failure to both materials. Research studies clearly indicated fire performances of cementitious material are affected by the mineral additives like fly ash. However, currently very little information is available on the performance evaluation of high volume fly ash grout exposed to elevated temperature. An understanding of various factors influencing fire performance will aid in developing appropriate solutions for mitigating spalling and enhancing fire resistance of concrete grouting materials. This paper discusses the fly ash grout's characteristics under elevated temperatures and effect of different types of cooling method, curing durations and fly ash content. The specimens were water cured for 28, 90, 180 and 360 days. Loss of weight and compressive strengths of OPC and fly ash grouts (10, 20, 30, 40, 50% of fly ash) exposed to high temperatures (200, 400, 600, 800 and 1000ºC) and cooled in air and water were obtained. It was observed that the compressive strength of the air cooled grout increased with an increase in the temperature up to 400 ºC; while the water cooled grout reduces strength with increase in temperature. Fly ash grout exhibited better resistance to strength loss when exposed to elevated temperature. The type of cooling affects the intensity of cracks formation, residual weight and also the compressive strength, the effect being more pronounced as the fly ash and temperature increases. These results were also supported by scanning electron microscope (SEM) studies which reveal the formation of ettringites in OPC mortar post exposure. The overall result indicated that fly ash grout could be benefiting in the construction due to better resistance to high temperature.